PENGGUNAAN PUZZLE SEBAGAI MEDIA PEMBELAJARAN BAHASA ANAK USIA 4–5 TAHUN DI PAUD A. SOPYAN - Karwati, Karwati; Arifudin, Opan; Chusnarin Haryanti, Heny (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Language is a crucial aspect of early childhood development as it serves as a means of communication, thinking, and understanding the environment. Preliminary observations at PAUD A. Sopyan Tamansari, Pangkalan, Karawang revealed that the language skills of children aged 4–5 years were still underdeveloped. Puzzle games, which should function as educational media, were mainly used as fillers without structured strategies. This study aims to examine the effectiveness of using puzzles as a learning medium to enhance children's language development. The research employed a descriptive qualitative method involving 15 children aged 4–5 years and a classroom teacher as subjects. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The findings show that puzzle activities stimulated children’s abilities to ask questions, name pictures, recognize letters, and answer questions. Of the 15 children, 7 (46.67%) were in the “Beginning to Develop” category, 7 (46.67%) were “Developing as Expected,” and 1 (6.67%) was “Developing Very Well.” Thus, puzzles are considered effective as an alternative learning medium to improve early childhood language skills when applied in a structured and consistent manner.